History and Facts about Black Holes - Khatiwoda, Devandra (Himalayan Physics, 2011)
Not available. Key words: Black holes The Himalayan Physics Vol.1, No.1, May, 2010 Page: 90-92 Uploaded Date: 28 July, 2011